Análise dos índices de conformidade e homogeneidade de planejamentos radioterápicos com feixes de fótons - Rombaldi, Paulo Vitor Lopes [UNESP] (Universidade Estadual Paulista (Unesp), 2019)
The study consisted in evaluating the homogeneity index (HI) and the conformity index (CI) of the radiation dose distribution in three-dimensional radiotherapy plans in prostate cancer. The research was carried out with the Eclipse Treatment Planning System (TPS) of the Varian Medical Systems, available at the Technical Section of Radiotherapy of the Clinical Hospital in Botucatu Medical School (HC-FMB). A total of 30 (thirty) three-dimensional radiotherapy (RT-3D) planning of prostate tumors performed in the routine of the service were analyzed. The CI and HI values for each of the clinical cases analyzed were calculated using the mathematical expressions considered in the literature and the radiation dose distribution values corresponding to the percentages of prostate volume and planning target volumes (PTV), as indicated in the dose-volume histogram (DVH) of each of the effective treatment plans. The results showed that 60% of the plans reached satisfactory CI values while 70% achieved HI values within acceptable for a good three-dimensional computerized radiotherapy planning

O estudo consistiu em avaliar o índice de homogeneidade (IH) e o índice de conformidade (IC) da distribuição de dose de radiação em planejamentos tridimensionais de radioterapia em câncer de próstata. A pesquisa foi realizada com o Sistema de Planejamento de Tratamento (TPS) Eclipse da fabricante Varian Medical Systems, disponível no Setor Técnico de Radioterapia do Hospital das Clínicas da Faculdade de Medicina de Botucatu (HC-FMB). Foram analisados 30 (trinta) planejamentos radioterápicos tri-dimensionais (RT-3D) de tumores da próstata, realizados na rotina do serviço. Os valores de IC e IH para cada um dos casos clínicos analisados foram calculados usando as expressões matemáticas consideradas na literatura e os valores de distribuição de dose de radiação correspondentes aos percentuais de volume prostático e volumes alvos de planejamento (PTV), conforme indicados no histograma dose-volume (DVH) de cada um dos planos de tratamento efetivados. Os resultados mostraram que 60% dos planejamentos atingiram valores de IC satisfatório enquanto que 70% conseguiram valores de IH dentro do aceitável para um bom planejamento radioterápico tri dimensional computadorizado
Analysis of conformity and homogeneity indexes of radiotherapy planning with photon beams
Keywords: Conformity indexes; Homogeneity indexes; Radiotherapy; Radiotherapy planning system; Índice de homogeneidade; Radioterapia; Sistema de planejamento radioterápico; Índice de conformidade